Sustainability Reporting: Framing Theory and Rhetoric Theory Perspectives - Kurniawati, Endah; Budiyanto; Budi Raharjo, Ikhsan (International Journal of Accounting and Economics Studies, 2025)
This study explores the use of framing and rhetoric strategies in PT. X’s sustainability reporting from 2021 to 2023, analyzed through the lenses of Framing Theory, Rhetoric Theory, Legitimacy Theory, and Stakeholder Theory. As a major player in Indonesia’s digital economy, PT. X faces significant scrutiny regarding its environmental and social responsibilities. The findings reveal that the company employs a dominant framing strategy that highlights innovation and progress, portraying sustainability as a long-term vision rather than an immediate responsibility. Through selective data presentation and optimistic narratives, PT. X constructs a positive public image, often downplaying operational challenges and trade-offs. Rhetorical elements—Logos, Pathos, and Ethos—are extensively used to build legitimacy and trust. Quantitative data and references to global standards (Logos), emotional storytelling (Pathos), and the inclusion of third-party certifications and partnerships (Ethos) are central to their approach. These strategies help reinforce the company’s reputation among investors, regulators, and other stakeholders. However, the findings also indicate a risk of greenwashing, as transparency is occasionally compromised in favor of strategic communication. The study contributes theoretically by linking narrative construction with legitimacy and stakeholder engagement. Practically, it suggests that a more balanced reporting approach—one that includes transparent disclosures of both achievements and limitations—would enhance credibility. Ultimately, the research underlines the need for sustainability reports to evolve beyond branding tools toward instruments of genuine accountability.